Implementasi Pendidikan Transformatif melalui Pembelajaran Berbasis Riset dan Proyek di Sekolah Dasar - Muhammad Amzar; Suardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of transformative education through research- and project-based learning in elementary school. The background of this study is the dominance of teacher-centered learning practices that limit students’ critical thinking, creativity, and social awareness. This research was conducted at SDN 151 Inpres Kalampa, Takalar Regency, using a qualitative approach. Data were collected through observation, interviews, and documentation involving the principal, teachers, and students. The results show that transformative learning practices have begun to develop through contextual learning activities, group discussions, and simple projects related to students’ real-life environments. However, several challenges were identified, including limited teacher understanding of transformative education concepts, time constraints, and the persistence of conventional learning culture. Despite these challenges, the school has strong potential to develop into a progressive elementary school supported by a conducive learning environment, positive teacher–student relationships, and strong religious and national values. This study concludes that transformative education is relevant and applicable in elementary schools and requires systematic teacher capacity building and collaborative school culture to ensure sustainability.